2011
DOI: 10.1111/j.1744-7429.2011.00751.x
|View full text |Cite
|
Sign up to set email alerts
|

Subtle Land‐Use Change and Tropical Biodiversity: Dung Beetle Communities in Cerrado Grasslands and Exotic Pastures

Abstract: Although many tropical savannas are highly influenced by humans, the patterns of biodiversity loss in these systems remain poorly understood. In particular, the biodiversity consequences of replacing native grasslands with exotic pastures have not been studied. Here we examine how the conversion of the native savanna grasslands affects dung beetle communities. Our study was conducted in 14 native (grassland: campo limpo), and 21 exotic (Urochloa spp. monoculture) pastures in Carrancas, Minas Gerais, Brazil. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 49 publications
5
52
0
5
Order By: Relevance
“…forests and Amazonian secondary forests, savannahs and agricultural areas , Louzada et al 2010, Matavelli & Louzada 2008. The number of dung beetle species and individuals reported here was lower than in other intra-Amazonian savannahs (Louzada et al 2010, Matavelli & Louzada 2008, southern cerrado (Abot et al 2012, Almeida et al 2011, Durães et al 2005, Gries et al 2012, Vieira & Silva 2012 and native grasslands of the 'Pampa' region . We believe this lower species-rich sample can be due the historical isolation of the intra-Amazonian from the cerrado savannahs in central Brazil during the Pleistocene period (Sanaiotti et al 2002), besides some natural specific habitat characteristics, such as edaphic factors, vegetation structure and fire occurrence (Barbosa & Fearnside 2005, Louzada et al 2010).…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…forests and Amazonian secondary forests, savannahs and agricultural areas , Louzada et al 2010, Matavelli & Louzada 2008. The number of dung beetle species and individuals reported here was lower than in other intra-Amazonian savannahs (Louzada et al 2010, Matavelli & Louzada 2008, southern cerrado (Abot et al 2012, Almeida et al 2011, Durães et al 2005, Gries et al 2012, Vieira & Silva 2012 and native grasslands of the 'Pampa' region . We believe this lower species-rich sample can be due the historical isolation of the intra-Amazonian from the cerrado savannahs in central Brazil during the Pleistocene period (Sanaiotti et al 2002), besides some natural specific habitat characteristics, such as edaphic factors, vegetation structure and fire occurrence (Barbosa & Fearnside 2005, Louzada et al 2010).…”
Section: Resultsmentioning
confidence: 63%
“…Most species we found belong to species-clusters that have been collected within dry, open and highly disturbed environments on the American continent, some of them with records from Argentina (Damborsky et al 2015), Mexico (Novelo et al 2007), Ecuador (Carpio et al 2009), Venezuela (Lozano 2010), Colombia (Noriega et al 2007) and Costa Rica (Padilla-Gil & , coastal low land forests ('Tabuleiro' forests) (Endres et al 2007) and native and exotic pasturelands (Almeida et al 2011, Costa et al 2009. In addition, the species reported here were also found within highly impacted Brazilian forests, such as northeastern fragments of Atlantic forest (Salomã o & Iannuzzi 2015, Viegas et al 2014, planted Eucalyptus sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conditions for these dung balls will depend on soil texture, humidity and temperature, all of which vary across the landscape (Halffter and Matthews, 1966;Halffter, 1991). The greatest diversity of dung beetles is found in well-preserved environments where communities may have distinct structures and feeding guilds (Halffter, 1991) and which are sensitive to variation in soil conditions (Almeida et al, 2011;Halffter et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…This was verified in Coleoptera (Halffter and Through environmental heterogeneity, studies have shown that disturbances in vegetation structure resulting from human or animal activity are harmful to insect fauna and cause a reduction in both diversity and abundance (Fonseca and Diehl, 2004;. In addition, replacing native vegetation with exotic species, often montypic, e.g., areas with Pinus spp., can directly interfere with the richness and abundance of insects (Romero-Alcaraz and Ávila, 2000; Ganho and Marinoni, 2006; Almeida et al, 2011).…”
Section: Introductionmentioning
confidence: 99%